Developing and Assessing the Validity of a Scale to Assess Pet Dog Quality of Life: Lincoln P-QoL - Hall, Sophie S.; Brown, Beverley J.; Mills, Daniel S. (Frontiers in Veterinary Science, 2019)
There has been little investment in exploring the impact of the child-dog relationship on the dog. Since child-dog interactions can pose potentially serious threats to a dog’s physical and psychological health, as well as the wider satisfaction of the owner with their dog, we describe the development and validation of an owner-completed pet dog quality of life scale (Lincoln P-QOL), to enable professionals and families to monitor dog wellbeing and employ suitable interventions as required. Four-hundred and two dog-owners (194 lived with a neuro-typically developing child; 208 lived with a child with a neuro-developmental disorder) responded to an online survey. Respondents recorded whether they had observed their dog displaying any of the 22 behavioural responses which have been identified as being common in 11 child-dog interactions. These behavioural responses appeared to group into three categories of behaviours (i.e. behavioural constructs), representing Excitability, Calmness and Fearfulness in the dog. To assess convergent validity of the quality of life scale respondents completed additional measures including, dog body condition score, health issues (incorporating psychological factors such as anxiety and physical proxies of wellbeing, such as skin irritations) and dog-owner relationship satisfaction. Excitability and Fearfulness constructs were associated with a negative impact on dog health and the owner-dog relationship. Calmness was associated with a positive impact on the dog-owner relationship. A range of interactions, including carefully expressed child-dog physical affection and spending quiet time together appear to had a beneficial impact on dog quality of life, whereas rough contact, child meltdowns and grooming/bathing had a negative effect. We found little evidence to support a difference in the overall quality of life of dogs living with neuro-typically developing children compared to those with a neuro-developmental disorder. However, parents and practitioners need to be aware of the potential increased risk to dog wellbeing when meltdowns, grooming/bathing and quiet time involve a child with a neuro-developmental disorder. This is the first validated scale for the assessment of dog wellbeing around children, additionally, the behavioural constructs identified may form the rational basis of a more general dog behaviour/stress assessment tool in social situations.